The quantification of game-induced muscle fatigue in amputee soccer players - Simim, M. A.; Bradley, P. S.; da Silva, B. V.; Mendes, E. L.; de Mello, M. T.; Marocolo, M.; da Mota, G. R. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: This study quantified the degree of game-induced muscular fatigue in amputee soccer players.